A CULTURAL AND HISTORICAL CASE STUDY: THE OLDEST SUN TEMPLE IN MUMBAI - Bhat, Jaiee Suhas (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Lord Surya, or the Sun God, has long been regarded as one of the most important and popular celestial deities in Indian religious tradition. Since the time of the Harappan Civilization, the Indian subcontinent has witnessed the worship of various natural forces, among which the sun has held a central place as a source of light, energy, and strength. Despite this deep-rooted reverence, there are surprisingly few prominent Sun temples in India, the reasons for which remain largely unexplored. One such lesser-known temple is the 117-year-old Sri Suryanarayana Mandir located in Bhuleshwar, in the southern part of Mumbai. This temple remains relatively obscure and under-researched. The present study aims to examine the historical background and religious significance of the Sri Suryanarayana Mandir, while also exploring the various forms and practices of Saur Puja observed there. The research will draw on case studies, field visits, and relevant secondary sources to shed light on this often overlooked aspect of India’s religious heritage.